Tracing the technological trajectory of coal slurry pipeline transportation technology: An HMM-based topic modeling approach - Wang, Jinfeng; Li, Kang; Feng, Lijie (Frontiers in Energy Research, 2022)
Coal slurry pipeline transportation is an important way to realize green coal logistics. To capture the trend and the development characteristics of coal slurry pipeline transportation technology and improve the efficiency of research and development (R&D), this study attempts to trace and predict the technology trend from patent texts through the stochastic process analysis of topic evolution. As a result, this study extracts potential technology topics from patent text by using the Latent Dirichlet Distribution method. Then, a Word2vec-based topic word vector model is applied to calculate the cosine similarity between topics, and an evolutionary trend model based on a hidden Markov model is constructed. Finally, it is used to analyse and predict trends in the technological evolution of this field. It was found that the advancement of technology related to pulping is fundamental to promoting the development of coal slurry pipeline transportation technology, which is also a common research topic. Finally, technologies related to pipeline transportation capacity enhancement and the industrial application of coal slurry will be the focus of future R&D in this field with broad research and application prospects.